Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2151/jmsj.2004.397
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Kelvin Waves Observed with GPS Occultation Measurements (CHAMP and SAC-C)

Abstract: Structure and propagation of equatorial Kelvin waves during May 2001 and December 2002 are observed from the temperature profiles in the upper troposphere and the lower stratosphere using CHAMP and SAC-C GPS radio occultation data. Kelvin waves derived from temperature fluctuations characterize eastward phase propagation in time-longitude section and eastward phase tilts with height in altitude-longitude section between 10 and 30 km. The phase progression spans the range indicating the continuity of Kelvin wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 21 publications
7
52
0
Order By: Relevance
“…In addition, balloons were released eight times a day for five days during the intensive observation period ( (739) and 65% (552) ascended higher than 25 km and 30 km, respectively. Consistent with earlier balloon studies (e.g., Tsuda et al 2004), the balloons generally reached higher altitudes (by approximately 2 km on average) during the daytime compared to the nighttime, with the maximum difference at PD (4.1 km). However, at KL and SG, balloon burst occurred at lower altitudes during the daytime, as shown in Table 2.…”
Section: Datasupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, balloons were released eight times a day for five days during the intensive observation period ( (739) and 65% (552) ascended higher than 25 km and 30 km, respectively. Consistent with earlier balloon studies (e.g., Tsuda et al 2004), the balloons generally reached higher altitudes (by approximately 2 km on average) during the daytime compared to the nighttime, with the maximum difference at PD (4.1 km). However, at KL and SG, balloon burst occurred at lower altitudes during the daytime, as shown in Table 2.…”
Section: Datasupporting
confidence: 89%
“…In order to see the horizontal structure of the waves, simultaneous CHAMP/ GPS RO observations are utilized. For extraction of Kelvin waves with zonal wave numbers of 1 and 2 from GPS RO data, the procedure implemented by Tsai et al (2004) is closely followed. We selected the latitude within G10 from equator in order to avoid mixing of waves other than the Kelvin waves, with the height coverage of 10-30 km.…”
Section: Long-period Oscillations (Kelvin Waves)mentioning
confidence: 99%
See 2 more Smart Citations
“…Highly accurate and relatively better vertical resolution (@100 m) of temperature measurements in the troposphere and lower stratosphere have become possible with the advent of the GPS radio occultation technique. Using the GPS measurements, Tsai et al (2004) showed evidence of Kelvin waves spanning the upper troposphere and lower stratosphere (UTLS) region. Randel and Wu (2005) further extended the analysis and observed long-period (@20 days) waves with short vertical wavelengths of 4-8 km.…”
Section: Introductionmentioning
confidence: 99%